Simulating the effects of coated ice nuclei in the formation of thin ice clouds in the high arctic using RAMS - Seigel, Robert, author; Cotton, William, advisor; Stephens, Graeme, advisor; Fassnacht, Steven, committee member; Carrió, Gustavo, committee member (Colorado State University. Libraries, 2010)
The Polar regions are an integral part of Earth's energy budget, however they are poorly understood mainly due to their remoteness and lack of observations. The recent launch of two successful satellites, CloudSat and CALIPSO, into the A-Train constellation are providing excellent insight into wintertime clouds and precipitation at the Poles. One distinguishable characteristic seen from satellite data during Arctic winter and spring is an optically thin cloud containing ice crystals large enough to precipitate out. These "thin ice clouds" (TIC) occur in regions affected by anthropogenic pollution. It is hypothesized that the anthropogenic pollution, likely sulfuric acid, coat the available ice forming nuclei (IN) and render them inactive for forming ice crystals. Therefore, the effective IN concentrations are reduced in these regions and there is less competition for the same available moisture leading to the formation of relatively small concentrations of large ice crystals. The ice crystals grow large enough for sedimentation, which dehydrates the Arctic atmosphere. We use Colorado State University's Regional Atmospheric Modeling System (RAMS) configured as a cloud resolving high-resolution model (CRM) with horizontal grid-spacing of 1 00m to simulate these TI C's. Varying ice nuclei (IN) concentrations from 5 L-1 to 100L-1 are used to simulate the effects of the acidic coating, whereby the low IN concentration represents the IN particles containing the acidic coating. Results show no concrete evidence in support of the hypothesis. Therefore, a sensitivity experiment is conducted to identify the environmental conditions that maximize the production of TIC's. Results indicate that an increase in both the temperature and supersaturation relative to observations provide a better environment for the production of TIC's.
Covers not scanned.
Keywords: Ice clouds; Ice nuclei